Effects of Exercise and Nutrition on the Coagulation System During Bedrest Immobilization. Issue 38 (September 2015) - Waha, James E.; Goswami, Nandu; Schlagenhauf, Axel; Leschnik, Bettina; Koestenberger, Martin; Reibnegger, Gilbert; Roller, Regina E.; Hinghofer-Szalkay, Helmut; Cvirn, Gerhard; Dora., Zelena
<x xml:space="preserve">Abstract</x> Abstract Immobilization in hospitalized medical patients or during simulation of spaceflight induced deconditioning has been shown to be associated with loss of muscle mass and bone. Resistance vibrating exercise (RVE) and/or high protein diet are countermeasures, which are capable of mitigating the adverse effects of immobilization. We investigated the effect of these countermeasures on the coagulation system. Two groups of volunteers, each of whom performed such countermeasures, were enrolled in the study. Volunteers, who did nothing while bed rested, served as controls. The berest and the intervention protocols were carried out at Clinique d' Investigation, MEDES, Toulouse, France. Eleven healthy men volunteered for this randomized crossover study. The subjects underwent 21 day of 6° head down bed rest (HDBR) followed by a washout period of 4 months. The first group followed an exercise schedule using resistance-vibrating exercise (RVE group). The second group also used the RVE but complemented it with high-protein supplement diet (NeX group). The third group only did bed rest. The highly sensitive methods calibrated automated thrombography (CAT) and thrombelastometry (TEM) were applied to monitor hemostatic changes. In all 3 groups, the hemostatic system shifted toward hypocoagulability during bed rest. For example, peak and thrombin formation velocity (VELINDEX) reduced in this period. Interestingly, a tendency toward hypercoagulation was observed during re-ambulation. In all 3 groups, ttPeak and StartTail were reduced, and Peak and VELINDEX (except in the RVE group) were significantly higher in relation to baseline values. Influence of bed rest on the coagulation system in the 2 groups performing countermeasures (RVE and NeX group) was the same as in the control bed-rested group. Clotting does not seem to be worsened by prolonged immobilization, or by countermeasures such as RVE/exercise or high-protein supplementation during immobilization. Therefore, only hospitalized medical patients at an elevated risk for thrombosis should be treated with anticoagulants. However, clinicians have to be aware that the re-ambulation period following immobilization might be associated with an elevated risk of thrombotic events.